The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.3390/md11124799
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to the Neurotoxic Dinoflagellate, Alexandrium catenella, Induces Apoptosis of the Hemocytes of the Oyster, Crassostrea gigas

Abstract: This study assessed the apoptotic process occurring in the hemocytes of the Pacific oyster, Crassostrea gigas, exposed to Alexandrium catenella, a paralytic shellfish toxins (PSTs) producer. Oysters were experimentally exposed during 48 h to the toxic algae. PSTs accumulation, the expression of 12 key apoptotic-related genes, as well as the variation of the number of hemocytes in apoptosis was measured at time intervals during the experiment. Results show a significant increase of the number of hemocytes in ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 53 publications
(63 reference statements)
4
32
0
Order By: Relevance
“…gigas (Medhioub et al 2013). Altogether, these data support a mechanism for PST-induced apoptosis in bivalve hemocytes that is independent of ROS production.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…gigas (Medhioub et al 2013). Altogether, these data support a mechanism for PST-induced apoptosis in bivalve hemocytes that is independent of ROS production.…”
Section: Discussionsupporting
confidence: 61%
“…Previous studies have shown that PSTproducing algae increase the mortality of C. gigas hemocytes both in vitro (Hegaret et al 2011;Lassudrie et al 2016) and in vivo (Medhioub et al 2013). However, fundamental features of this process, including key mechanistic details of how specific PSTs cause toxicity, remained poorly characterized.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both in vivo and in vitro infections were shown to result in hemocyte phagocytosis, respiratory burst and finally in apoptosis (Goedken et al, 2005). In addition, detoxification of environmental pollutants, including of toxic substances produced by harmful algal blooms, has been shown to induce massive apoptotic death among the hemocyte population in bivalves (Medhioub et al, 2013;Ray et al, 2013;Yao et al, 2013;Prado-Alvarez et al, 2013). Finally, a physiological process not related to immune defense, shell mineralization, also leads to an important loss of hemocytes because it requires the migration of numerous hemocytes to the surface of the shell-facing outer mantle epithelium (Mount et al, 2004).…”
Section: Research Articlementioning
confidence: 99%